Tissue imaging with scanning acoustic microscopy and raman spectroscopy - Parlak, Melita. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
The morphological and mechanical characteristics of tissues are critical in biology and medicine. Furthermore, external agents might cause various modi cations in the biological samples that alter the physiological properties. Thus, studying the mechanical and optical properties of tissue is vital in the theranostic processes of the diseases. For characterizing the acousto-mechanical properties of biological samples, scanning acoustic microscopy (SAM) is introduced as an imaging method. We used the colloidal semiconductor quantum dots (QD's) as contrast agents for SAM. Since QD's aggregation is signi cant, especially in targeted nanoparticle-based drug delivery systems, the acoustic impedance values of aggregated QD were measured with SAM. It turns out that the acoustic impedance values are proportional to the volume and the heterogeneity of aggregation. Also, we studied liver tissues of rats exposed to phthalates, which were applied to modify the exibility. Therefore, the mechanical properties of tissues varied. Apart from SAM, Raman spectroscopy is another sensing tool that uses light to characterize the tissue. Raman spectrum provides molecular information since the peaks in the spectra represent the vibrational transition energies of the chemical bonds in the sample. In this thesis, we also investigated the Raman spectra (RS) of rat liver tissues that were exposed to phthalate and the ones that were not exposed. We showed that DNA, protein, and the lipid/collagen structure changed due to exposure to phthalate esters. As a result, this thesis revealed that SAM and RS techniques could determine and con rm mechano-chemical alterations of the biological samples.
Keywords: Tissues -- Mechanical properties.; Biomechanics.